SELF-DETERMINATION OF THE KURDES IN SYRIA: ORIGINS, FORMS AND INTERNATIONAL PROSPECTS - M. Dyurre (Vestnik MGIMO-Universiteta)
The article addresses the problem of self-determination of the Kurdish ethnos in Syria. Kurds are an indigenous people in this territory and for a long time lived within a single space within the Ottoman Empire. The artificial division of the Middle East into states in the interests of European powers led to ignoring the interests and rights of the Kurdish ethnos. Self-organization of Kurds in Syria occurred gradually and mainly under the influence of external factors. The first one was the political activity of Kurds in neighboring countries, the second – the assimilation efforts of the Syrian authorities. Although the Kurdish population, basically, retained its identity, half a century of assimilation policy led to the erosion of the Kurdish ethnic enclaves in the north of the country. Moreover, self-organization and political mobilization of Kurds in Syria began to be accompanied by disagreements and splits of the main political forces. Kurdish political parties sought to act as a “third force” in the course of the civil war in Syria. However, disagreements prevented this, as well as certain pressure from Western countries, which pushed the Syrian Kurds to support the moderate opposition. The power vacuum in the north of Syria was able to fill the center-left party “Democratic Union”. This political force is in contact with the official Syrian authorities and, at the same time, receives US support. Created by the efforts of the “Democratic Union” the Kurdish autonomy in the north of the country provides stability in territories with the Kurdish and mixed populations, and also performs socio-economic functions. This makes the Kurdish autonomy an important element of negotiations about the future political structure of Syria.